A Review of State‐of‐the‐Art Microfluidic Technologies for Environmental Applications: Detection and Remediation. Issue 1 (21st September 2018) - Yew, Maxine; Ren, Yong; Koh, Kai Seng; Sun, Chenggong; Snape, Colin
Abstract: Microfluidic systems have advanced beyond natural and life science applications and lab‐on‐a‐chip uses. A growing trend of employing microfluidic technologies for environmental detection has emerged thanks to the precision, time‐effectiveness, and cost‐effectiveness of advanced microfluidic systems. This paper reviews state‐of‐the‐art microfluidic technologies for environmental applications, such as on‐site environmental monitoring and detection. Microdevices are extensively used in collecting environmental samples as a means to facilitate detection and quantification of targeted components with minimal quantities of samples. Likewise, microfluidic‐inspired approaches for separation and treatment of contaminated water and air, such as the removal of heavy metals and waterborne pathogens from wastewater and carbon capture are also investigated. Abstract : The latest advances in microfluidic technologies for environmental applications are reviewed, covering microdevices for detecting environmental samples of interest to droplet microfluidic synthesis of functional materials for environmental remediation, including water treatment and carbon capture and storage. A critical analysis of the current status and challenges and opinions on the future development of the rapidly developed technologies are also presented.